PATROL: a comprehensive reputation-based trust model. (13th August 2007) - Tajeddine, Ayman; Kayssi, Ayman; Chehab, Ali; Artail, Hassan
In this paper, we present PATROL, a general and comprehensive reputation-based trust model for distributed computing. The proposed model is an enhancement over our previous model, TRUMMAR, and aims at achieving a truly unique model that incorporates most concepts that are essential to determining trust-based decisions. Among the concepts upon which the trust model is based are reputation values, direct experiences, trust in the credibility of a host to give recommendations, decay of information with time based on a dynamic decay factor, first impressions, similarity, popularity, activity, cooperation between hosts, in addition to a hierarchy of host systems. The simulations performed on this model confirm its correctness and its adaptability to different environments and situations.